The effect of bovine serum albumin and fetal calf serum on sperm quality, DNA fragmentation and lipid peroxidation of the liquid stored rabbit semen - Sarıözkan, S; Türk, G; Cantürk, F; Yay, Ah; Eken, A; Akçay, A (My University, 2013)
The aim of the present study was to determine the effects of the bovine serum albumin (BSA) and fetal calf serum (FCS) on sperm quality, DNA fragmentation and lipid peroxidation of liquid stored rabbit semen stored up to 72 h at 5 C. Ejaculates were collected from five New Zealand male rabbits by artificial vagina and pooled at 37 C following evaluation. Each pooled ejaculate was split into three equal experimental groups and diluted to a final concentration of approximately 40 106 sperm/ml (single step dilution), in an Eppendorf tube, with the Tris based extender containing BSA (5 mg/ml), FCS (10%) or no additive (control) at 37 C, cooled to 5 C and stored for up to 72 h. The extender supplemented with BSA and FCS did not improve the percentages of motility and acrosomal abnormality during 48 h compared to the control. The additives BSA and FCS had a significant effect in the maintaining of plasma membrane integrity between 48 and 72 h storage period, compared to the control (P < 0.01). The supplementation of BSA and FCS had a protective effect on motility (P < 0.05), plasma membrane integrity (P < 0.01) and acrosomal integrity (P < 0.01) at 72 h compared to the control. The supplementations with BSA and FCS led to a reduction in DNA damage of rabbit sperm at 48 and 72 h during storage period, compared to the control (P < 0.001). Although supplementation of BSA and FCS caused significant (P < 0.01) decreases in malondialdehyde (MDA) level at 48 h and 72 h, they significantly (P < 0.01) increased the glutathione peroxidase (GPx) antioxidant activity up to 72 h when compared to the control group. In conclusion, BSA and FCS supplementation to liquid stored rabbit semen provide a protection for spermatozoa against cool storage-induced DNA damage and plasma membrane integrity by their antioxidative properties.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Rabbit Semen BSA FCS Liquid storage Lipid peroxidation Antioxidant activity DNA integrity